GAMBARAN PENGETAHUAN REMAJA AKHIR TERHADAP SIKAP DETEKSI DINI KANKER PAYUDARA - Ni’mah Mufidah; sinta Anggariyanti (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
This study aims to determine the final knowledge overview in conducting SADARI. This study used a quantitative descriptive approach with a cross-sectional approach. The population was late adolescents, with a sample of 100 using a purposive sampling technique. Research results show that knowledge about breast cancer among late adolescents is quite good. BSE practices among late adolescents are quite good, but not yet performed correctly. The behavior of BSE carried out by late adolescents requires habituation and health education from health workers so that BSE is carried out routinely as an early detection of breast cancer.